Perception towards the factors that affect the effectiveness of entrepreneurship training programme - Nor Shuhada Ahmad Shaupi; Mohd Rafi Yaacob; Azlinda Shazneem Md Shuaib (Faculty of Entrepreneurship and Business,UMK, 2015)
Entrepreneurship is important to economic development due to society development in economies where entrepreneurs can operate flexibly, develop their ideas, and gain the rewards. Nowadays, the government encourage the entrepreneur to participate in Entrepreneurial Training Programme to ensure their capabilities and sustainability in impressive level. However, the training programme has to take initiative to ensuring the effectiveness on such training. Thus, this paper aims to explore the towards the Factors that Affect the Effectiveness of Entrepreneurship Training among UMK’s students.. To achieve these objectives, the study adopted purposive sampling method to collect primary data through the structured questionnaire. A total sample of 50 students in Faculty of Entrepreneurship and Business, UMK were used as respondents. The result shows that the trainee’s readiness and learning approach are determinant to ensure the effectiveness of training programme. The results also show that there is a significant relationship between two variables which contribute to the effectiveness entrepreneurship training programme. Based on the research findings, the determinant of trainee effectiveness and learning approach unable to determine such of entrepreneurship training programme may provide (1) gain entrepreneur skills, (2), training programme more effective and (3) develops programs to increase global entrepreneurship